Desain Interior Perpustakaan sebagai Pendukung Kenyamanan pada Ruang Koleksi Anak - Ariska Idamayanti (Nazharat: Jurnal Kebudayaan, 2024)
This research uses a literature review method which involves searching, selecting and analyzing relevant literature from electronic databases such as Google Scholar and JSTOR. This research focused on the keywords "Library interior design" and "Children's collection room", and succeeded in identifying 58 articles from 2020 to 2024. Relevant articles were systematically extracted and analyzed based on research topics divided into two categories: interior design library and children's collection room. The results of the analysis show that good interior design is very important to create a library environment that is comfortable, functional and supports literacy activities, especially in the children's collection room. Design elements such as aesthetics, ergonomics, lighting, air circulation, sound, and harmonious design variations must be considered. In addition, children's libraries need to pay attention to safety, comfort and stimulating creativity through elements such as color, ergonomic furniture and interactive technology. In the context of Society 5.0, libraries must transform into inclusive and innovative public spaces to support digital literacy and the needs of modern society.